Performance Male and Female Drivers in Drowsiness System Based on Psychomotor Vigilance Task Test - Theresia Br. Pasaribu, Novie; ., Ratnadewi; Prijono, Agus; Pramono Adhie, Roy; Halim, Winda; Maini Heryanto, Rainisa (International Journal of Engineering and Technology, 2018)
Driving on the highway that takes a long time and monotonous often causes the motorist or motorcycle to feel fatigue. Fatigue can be divided into two: physical or motoric fatigue and psychological or mental fatigue. As a result of this fatigue the driver may feel drowsiness, loss of concentration that endangers the safety of the driver. Some literature distinguishes gender in ability or driving skills. This paper observed and measured gender differences in driving. Measurements using Psychomotor Vigilance Task to measure mental fatigue before and after the driver were given an Arithmetic Stress Test. The data obtained on experimental drivers of male and female will then be processed using statistical tests to find out whether the psychomotor vigilance task of female and male drivers have same performance or not. Statistical tests were performed using Paired Sample T-Test. We have 17 drivers with 13 men and 4 women, each taken 5 session obtained that the T-test value of session 1 to session 5 have the same result that is the performance male and female drivers has the same performance in fatigue, but the number of male driver collisions smaller than the number of female driver collisions.Â Â